Towards benchmarking youth engagement with adults in the Malaysian youth service through cross-national research - Krauss, Steven Eric; Ortega, Adriana; Abdullah, Haslinda; Hamzah, Azimi; Suandi, Turiman; Ismail, Ismi Arif; Ahmad, Nobaya (Institut Penyelidikan Pembangunan Belia Malaysia, 2013)
This paper reports on a current cross-national research initiative to study the effectiveness and impact of youth-adult partnerships (Y-APs) on developmental youth outcomes in four countries: the United States, Canada, Portugal and Malaysia. In Western contexts, Y-APs have been conceptualized as youth and adults working collaboratively for program or community action and are characterized by mutuality in teaching and learning as well as in program and organizational decision-making. Y-APs have been utilized as an effective tool for youth leadership development by engaging young people and adults in meaningful participation and working together for the sake of their organizations and communities. As Malaysia continues to move forwards toward its national goal of development and high-income status, there is a need to empower its youth by helping them acquire the needed skills and competences to fulfill their role as partners in national development. This paper puts forward the idea that Y-APs are a promising approach to further this aim, especially among Malaysian youth in the 18-to-25 year-old age group.